Elevated CO2 induces rapid dephosphorylation of plasma membrane H+‐ATPase in guard cells. Issue 6 (1st October 2022) - Ando, Eigo; Kollist, Hannes; Fukatsu, Kohei; Kinoshita, Toshinori; Terashima, Ichiro
Summary: Light induces stomatal opening, which is driven by plasma membrane (PM) H + ‐ATPase in guard cells. The activation of guard‐cell PM H + ‐ATPase is mediated by phosphorylation of the penultimate C‐terminal residue, threonine. The phosphorylation is induced by photosynthesis as well as blue light photoreceptor phototropin. Here, we investigated the effects of cessation of photosynthesis on the phosphorylation level of guard‐cell PM H + ‐ATPase in Arabidopsis thaliana . Immunodetection of guard‐cell PM H + ‐ATPase, time‐resolved leaf gas‐exchange analyses and stomatal aperture measurements were carried out. We found that light–dark transition of leaves induced dephosphorylation of the penultimate residue at 1 min post‐transition. Gas‐exchange analyses confirmed that the dephosphorylation is accompanied by an increase in the intercellular CO2 concentration, caused by the cessation of photosynthetic CO2 fixation. We discovered that CO2 induces guard‐cell PM H + ‐ATPase dephosphorylation as well as stomatal closure. Interestingly, reverse‐genetic analyses using guard‐cell CO2 signal transduction mutants suggested that the dephosphorylation is mediated by a mechanism distinct from the established CO2 signalling pathway. Moreover, type 2C protein phosphatases D6 and D9 were required for the dephosphorylation and promoted stomatal closure upon the light–dark transition. Our results indicate that CO2 ‐mediated dephosphorylation of guard‐cell PM H + ‐ATPase underlies stomatal closure.